Evaluation of Vitamin D Levels and Response to Therapy of Childhood Migraine - Betül Kılıç; Mustafa Kılıç (Medicina, 2019)
Background and Objectives: Vitamin D deficiency and insufficiency are related with many neurological diseases such as migraine. The aim of this study was to investigate whether pediatric migraine is associated with vitamin D deficiency and the effect of vitamin D therapy on the frequency, duration, severity of migraine attacks, and Pediatric Migraine Disability Assessment (PedMIDAS). Materials and Methods: We retrospectively examined the patients’ levels of calcium, phosphorus, parathyroid hormone, alkaline phosphatase, and 25-OH vitamin D of 92 pediatric migraine patients. The patients were divided into two groups: Group 1, which had low vitamin D levels and received vitamin D therapy, and group 2, which had normal vitamin D levels and did not receive vitamin D therapy. Migraine severity measured by the visual analog scale (VAS), migraine frequency, and duration as well as scores on the PedMIDAS questionnaire were compared with regard to the 25-OH vitamin D levels. In addition, pre- and posttreatment pedMIDAS scores, VAS, migraine frequency, and duration were compared with baseline values. Results: A total of 34.7% patients had vitamin D insufficiency (vitamin D levels between 10 and 20 ng/mL), whereas 10.8% had vitamin D deficiency (vitamin D levels < 10 ng/mL). Migraine frequency, migraine duration, and PedMIDAS scores were significantly higher in the group 1 than group 2 (p = 0.004, p = 0.008, and p = 0.001). After vitamin D therapy at sixth months of supplementation, migraine duration was reported statistically significant shorter (p < 0.001) and the migraine frequency, VAS scores, and pedMIDAS scores were statistically significant lower compared with baseline values in group 1 (p < 0.001). Conclusion: We found a marked correlation between pediatric migraine and vitamin D levels. Vitamin D therapy was beneficial in migraine pediatric patients.